Upaya Meningkatkan Keaktifan Dan Hasil Belajar Siswa Melalui Metode Think- Pair-Share (TPS) Pada Mata Pelajaran IPA Kelas Vc SD Muhammadiyah 1 Ketelan Surakarta - Bagaskara, Binawan (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to increase students' active learning in learning Sciences lesson through the Think-Pair-Share (TPS) method. The type of research is classroom action research (CAR). The method of collecting data is carried out through interviews, observation, documentation and test techniques. The results of this research show an increasing student activity and learning outcomes in science lesson through the Think-Pair-Share (TPS) method. This can be seen from: 1) Students' activeness in asking questions before taking the action is 17.50% and at the end of the action it reaches 71,43%, 2) Students' activeness in working on questions in front of the class and answering questions before taking the action is 27.50 % and at the end of the action reaches 77,14%, 3) Student activeness in discussions before carrying out the action is 27.50% and at the end of the action reaches 85,71%. Students who complete their studies before carrying out the action is 34,28% and at the end of the action reaches 94,28 % . These results show that the application of the Think-Pair-Share (TPS) method can increase the activeness and learning outcomes of students in Sciences lesson of Class 5C in SD Muhammadiyah 1 Ketelan Surakarta for the academic year 2020/2021